Hedging Dow Jones Islamic and conventional emerging market indices with CDS, oil, gold and the VSTOXX: A comparison between DCC, ADCC and GO-GARCH models - Nejib Hachicha; Ahmed Ghorbel; Mohamed Chiheb Feki; Sofiane Tahi; Fredj Amine Dammak (Borsa İstanbul Review, 2022)
Our goal in this paper is to examine the time-varying optimal hedging ratios for the Dow Jones Islamic and conventional emerging stock market indices, hedged with oil, gold, and the VSTOXX as well as four emerging-country sectoral CDS indices (raw materials, industry, health care, and telecommunications). Using a rolling-window procedure with daily data, for the period from January 2000 to April 2019, along with, DCC, ADCC and GO-GARCH models as well as a hedging effectiveness criterion, we determine the best hedging instrument(s). Our findings prove that CDS indices are the best hedging instruments for both Islamic and conventional portfolios, as they have the highest hedging effectiveness. Our empirical results are robust to distribution assumptions and to the use of three MGARCH models in examining different refits (20, 40, and 60 days).
Keywords: F36; G15; Q43; 330; ADCC; DCC; Dow Jones Islamic and conventional emerging market indices; GO-GARCH; Hedging effectiveness ratio; Sectoral CDS indices